Controllable release of nitric oxide and doxorubicin from engineered nanospheres for synergistic tumor therapy. (15th July 2017) - Tan, Lianjiang; Huang, Ran; Li, Xiaoqiang; Liu, Shuiping; Shen, Yu-Mei
Graphical abstract: Abstract: NaYF4 :Yb, Er upconversion nanoparticles (UCNPs) capped with long-chain carboxylic acid were synthesized and then conjugated with chitosan (CS) in the aid of N -hydroxysuccinimide. The resultant nanocompound was integrated with doxorubicin (DOX) and Roussin's black salt (RBS), a photosensitive nitric oxide (NO) donor to produce stimuli-responsive UCNPs(DOX)@CS-RBS nanospheres as nanocarriers for controllable drug delivery. On the one hand, the encapsulated UCNPs can efficiently absorb NIR photons and convert them into visible photons to trigger NO release. On the other hand, the entrapped DOX can be released at lowered pH from the swollen nanospheres caused by stretched oleoyl-CS chains under acidic conditions. The UCNPs(DOX)@CS-RBS nanospheres exhibit great therapeutic efficacy, which is attributable to the combination of NO and DOX releases based on NO dose-dependent mechanisms. This study highlights the controllable release of NO and DOX from the same nanocarriers and the synergistic therapeutic effect on tumors, which could give new insights into improving cancer nanotherapeutics. Statement of Significance: In this paper, core-shell structured UCNPs(DOX)@CS-RBS nanospheres have been designed and synthesized via a step-by-step procedure. The stimuli-responsive UCNPs(DOX)@CS-RBS nanospheres act as nanocarriers for controllable drug delivery towards cancer therapy. The encapsulated UCNPs can efficiently absorb NIR photons and convert them into visible light to trigger NO release. Meanwhile, the entrapped DOX can be released from the swollen nanospheres caused by stretched oleoyl-CS chains at lowered pH typical of intracellular environment. Synergistic cancer therapy will be achieved through the combination of NO and DOX releases based on NO dose-dependent mechanisms. This study provides new drug nanocarriers with high antitumor efficacy for synergistic cancer therapy.